CANDI PRAMBANAN PASCA GEMPA BUMI - Suryolelono, Kabul Basah (Civil Engineering Forum Teknik Sipil, 2007)
Prambanan Temple area was partially destroyed by Yogyakarta Earthquake on May 27th, 2006. The earthquake caused a lot of parts of temple to break and fall to pieces, but entirely the structure of the temple still stand, although it looks like wrapping. The mystery of Prambanan Temple is interesting to be investigated from geotechnical approach, for structural stability of the temple. The research was conducted by doing field investigation, consisted of boring and soil sampling, combined with geo-electrical and geo-radar investigation inside the area of the temple, for knowing the foundation structure conditions. The available secondary data of physical and mechanical properties of soil were obtained from laboratory investigations. Evaluation was conducted for soil layer and the location of groundwater level beneath the temple. From the observation results, it can be seen that the depth of original soil is of -14,00 m, from the yard of the temple, and bodies of the temple are located white stone (tuff) block of 8,00 m thick. The tuff block layer acts as a foundation. Groundwater level was found at the depth of 11,20 m from the yard of the temple. Under the foundation of the temple, there is a 6,00 m thick of compacted coarse sand layer, acts as a vibration energy damper. Â